The Role Of Digital Marketing Strategy In MSMEs - Amelia Warda; Emma Triana Sutedy; Nurlinda Burahima (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study looks on MSME company strategies that leverage technology, namely digital marketing during and after the epidemic. This research was carried out utilizing qualitative and descriptive methodologies. Researchers collected data via observation, interviews, and documentation in the Ulumanda region of Majene, West Sulawesi. The data was then evaluated utilizing interactive modeling approaches. According to the study findings, MSMEs are dealing with new, more significant issues such as restricted distribution, limited manufacturing, difficulties understanding market demands, more digitally savvy competition, and a reduction in sales and output. Finally, MSMEs must comprehend and utilize digital to solve this challenge. Digital marketing targets a wide range of nations and areas. Small and medium-sized enterprises must be robust when coping with digital difficulties. SWOT analysis helps small and medium-sized firms integrate digital technologies.